Analisis Yang Mempengaruhi Simpanan Tahun 2012-2014 (Studi Kasus Perbandingan Pada PT. Bank Negara Indonesia dengan PT. BNI Syariah) - Fadila, Aswinar; , Eny Setyowati.,SE.,MSi; , Imron Rosyadi, S.E., M.Si (2016)
The purpose of this study was to determine the direction and magnitude of the effect and the tax revenue sharing on Mudharabah savings function at PT. BNI Syariah; and how the direction and magnitude of the effect of interest rates and taxes on savings function at PT. BNI in the period 2012-2014 and to know there are significant differences between the savings on PT. BNI Syariah PT. BNI. This study analyzes the factors affecting savings in BNI and BNI Syariah services in Indonesia in 2012-2014. The research data using the Monthly Report PT. BNI Syariah, Monthly PT. BNI and Bank Indonesia (BI) using quarterly data from 2012 to 2014 time series. The analytical tool used in this study is a partial adjustment regression model (PAM: Partial Adjustment Model). Based on the PAM test results on the PT. BNI result is that the variable interest (X1) and no significant negative effect on deposits in BNI. Variable Tax (X2) positive and significant impact on deposits in BNI. PAM test results on the PT. BNI Syariah result is that variable variables Profit Sharing Ratio (X1) and no significant negative effect on deposits in BNI Syariah. Variable Tax (X2) and no significant positive effect on savings in BNI Syariah. Keywords: Profit Sharing Ratio, Interest Rates and Taxes.